Simulación del tiempo de vida útil del aceite de soya (Glycine max), utilizando pruebas aceleradas. - Ayala Godoy, Luis Alberto (2012)
Simulación del tiempo de vida útil del aceite de soya (Glycine max), utilizando pruebas aceleradas.